Manajemen Sumber Daya Manusia dalam Pengembangan Kualitas Guru Perspektif Undang-Undang Guru dan Dosen - Aswad, Chaeril; Mangenre, Muh. Fadli; Syamsuddin, Syamsuddin (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This case study research aims to determine human resource management in the development of teacher quality in one of the Islamic senior high school in South Sulawesi. Data was collected using observation, interviews and documentation. Sources of data in this study included the head of the madrasah, deputy head of the madrasah curriculum section, and teachers. The results of data analysis show that in developing teacher quality, madrasah heads do it in four ways, namely providing motivation, encouraging teachers to attend seminars, involving teachers in Subject Teacher Consultation (MGMP) activities, and involving teachers in education and training activities. Regarding teacher quality, there are four competencies that an educator must have that can support the quality of a teacher, namely pedagogic competence, personal competence, social competence and student professional competence.